Exploring Resilience among Elderly Widows in Nepal - Pant, Poonam (Tribhuvan University Journal, 2022)
Many traditional societies still lack a strong social security systems for the elderly people. They generally view elderly people living with family as dependent on the family structure for social support, health and wellbeing. However, widows lack privileges and protection even when they live in traditional joint families, with at least one child and grandchildren. In reality, their resilience plays a significant role in their health and wellbeing as they age. To identify research gap about resilience among elderly widows, this study assessed the situation of 25 elderly widows aged 65 and above residing with their families in Kathmandu district , Nepal and identified key factors bringing about resilience in their day-to-day life. The resilience index comprised of four dimensions: psychological, physical health and fitness, food and nutrition and life support. The findings indicate that financial independence and education are two critical factors that best support resilience in elderly widows. This has far-reaching impacts on vulnerable groups like elderly people, especially elderly widows. The resilience index will be helpful for policy makers, stakeholders and other researchers to study the wellbeing and resilience among older widows.